Left atrial spontaneous echo contrast in patients with permanent pacemakers. Issue 3 (September 1997) - Lee, T. M.; Su, S. F.; Chien, K. L.; Lin, Y. J.; Chen, W. J.; Chen, M. F.; Liau, C. S.; Lee, Y. T.
Abstract : OBJECTIVE: To determine the relations between left atrial appendage function, spontaneous echo contrast, and thromboembolism in patients with different modes of permanent pacemakers. PATIENTS AND METHODS: 88 patients with pacemaker implantation and 25 healthy controls in sinus rhythm had transoesophageal echocardiographic examination of the left atrial appendage. Left atrial size, appendage area, peak filling and emptying velocities of the atrial appendage, and the presence or absence of spontaneous echo contrast and thromboembolism were determined. The results in 63 patients with ventricular pacing (group 1, subdivided into subgroup 1A: 42 patients with sinus rhythm, and subgroup 1B: 21 patients with atrial fibrillation) were compared with those in 25 patients with synchronous pacing (group 2), and 25 normal control subjects (group 3). RESULTS: Patients with ventricular pacing had two distinct appendage flow patterns: well defined biphasic filling and emptying waves in subgroup 1A, and irregular very low filling and emptying waves in subgroup 1B. The ejection fraction of the left atrial appendage in subgroup 1A was significantly better than that in subgroup 1B (mean (SD) 40.6 (12.0)% v 7.6 (5.0)%, P < 0.0001). The spontaneous echo contrast was observed in 90% of subgroup 1B patients but in only 19% in subgroup 1A (P < 0.05) and was not found in groups 2 and 3 (P < 0.0001). There was a trend for increased prevalence of spontaneous echo contrast in subgroup 1A v group 2 (P = 0.053). Thrombi were detected in two cases, and cardiogenic embolism occurred in one case in subgroup 1B. All patients with spontaneous echo contrast had ventricular pacing. Multivariate analysis showed that atrial fibrillation was associated with occurrence of spontaneous echo contrast in patients with ventricular pacing (P = 0.005). CONCLUSIONS: The left atrial appendage ejection fraction was lower with ventricular pacing than with synchronous pacing. With ventricular pacing there was a trend towards increased prevalence of left atrial spontaneous echo contrast in patients in sinus rhythm, and a significantly increased prevalence in patients with atrial fibrillation.